Diversidade genética e estrutura populacional de Fasciola hepatica (Linnaeus, 1758): o papel dos hospedeiros definitivos - Schwantes, Jéssyca Bressan (2020)
Fasciola hepatica is a flatworm of the Trematoda Class, and is responsible for the disease called fasciolosis. This parasite is cosmopolitan and has heteroxenic cycle being dependent on two hosts to complete its life cycle: an mollusc of the Lymnaeidae family as intermediate host; and domestic (cattle, sheep, goats) or wild vertebrates as definitive hosts. In the American continent, Fasciola hepatica was introduced together with domestic animals at the beginning of European colonization, and since then, it was reported at least 14 South America native species to being infected, one of them is the capybara (Hydrochoerus hydrochaeris), which due to its semi-aquatic life habits has become an important reservoir of the parasite. This work aims to genetically characterize different populations of Fasciola hepatica in Brazil in different hosts (bovine and capybara). For that, adult parasites and feces from infected animals were collected for egg isolation in the states of Rio Grande do Sul and Paraná, and we used two fragments of the mitochondrial genes COI and NAD1 for genetic analysis. Nucleotide and haplotype diversity and number of haplotypes were evaluated. The haplotype relationship and the frequency of the haplotypes were calculated and haplotype networks were built by Median-joining. We performed the AMOVA test and calculated the fixation index (FST) to evaluate population structure. The genetic distance between parasites encountered on different hosts was calculated within each sampled host group and between host groups. Our results showed that the genetic structure of Fasciola hepatica, whether from domestic or wild animals, depends more on geographic aspects on than the host in question, in a way that the parasites of wild animals share the same gene pool as those from domestic animals from the same region. However, the high transit of domestic animals within the and the border control between Brazilian states lead to genetic homogeneity among populations within states and genetic structure between states. In the same way, when comparing the different hosts, wild animals from South America share the same population of parasites among them, and have parasites more genetically distant from those encountered in wild animals from the Old World. Therefore, the implementation of management plans on domestic and wild hosts must be carried out for the epidemiological control of Fasciola hepatica within the states of Rio Grande do Sul and Paraná, as well as the control of intermediate hosts, especially in the regions highly susceptive to the disease and with high potential to new definitive hosts.